2019
DOI: 10.1080/14330237.2019.1647494
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial needs of parents of adolescents who attempt suicide

Abstract: This qualitative study explored and described the psychosocial needs of parents of adolescents who had recently attempted suicide. Ten purposively selected parents (females = 10, age range 29 to 59) participated in semi-structured individual interviews on their lived experiences after their child attempted suicide. Thematic analysis of the data revealed the parents' psychological needs after the attempted suicide by their minor child to be characterized by emotional turmoil including feelings of regret, self-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Fourteen studies described participants' emotional reactions (Asare-Doku et al, 2017;Buus et al, 2014;Daly, 2005;Doyle et al, 2021;Dransart & Guerry, 2017;Garcia-Williams & McGee, 2016;Hellerova et al, 2022;Ngwane & van Der Wath, 2019;Nosek, 2008;Nygaard et al, 2019;Talseth et al, 2001;…”
Section: Descriptive Theme 11: Emotional Responses To Suicidal Behavi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies described participants' emotional reactions (Asare-Doku et al, 2017;Buus et al, 2014;Daly, 2005;Doyle et al, 2021;Dransart & Guerry, 2017;Garcia-Williams & McGee, 2016;Hellerova et al, 2022;Ngwane & van Der Wath, 2019;Nosek, 2008;Nygaard et al, 2019;Talseth et al, 2001;…”
Section: Descriptive Theme 11: Emotional Responses To Suicidal Behavi...mentioning
confidence: 99%
“…A study conducted in Ghana (Asare-Doku et al, 2017) identified social support as a coping resource for mothers, but not fathers, interpreted by the author as evidence of gendered responses to suicidal behaviour within the family. Some carers had sought professional emotional support, primarily in the form of individual counselling (Garcia-Williams & McGee, 2016;Nosek, 2008;Nygaard et al, 2019;Vandewalle et al, 2021;Wolk-Wasserman, 1987a) while others identified personal professional emotional support as an unresolved support need (Dransart & Guerry, 2017;Inscoe et al, 2021;Ngwane & van Der Wath, 2019;Wolk-Wasserman, 1987b).…”
Section: Descriptive Theme 12: Coping Alongside Suicide Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…stigma by association or courtesy stigma). For close persons a distinction can be made between persons caring for a person affected by suicidality [13][14][15], and persons who lost a close person by suicide [16][17][18]. In the latter case, stigma is linked to reduced psychological and somatic functioning and grief difficulties [19].…”
Section: Introductionmentioning
confidence: 99%
“…stigma by association or courtesy stigma). For close persons a distinction can be made between persons caring for a person affected by suicidality (13)(14)(15), and persons who lost a close person by suicide (16-18). In the latter case, stigma is linked to reduced psychological and somatic functioning and grief di culties (19).…”
Section: Introductionmentioning
confidence: 99%